CRITERIAL FEATURES OF PHYSICAL CULTURE TYPOLOGATION - Kuramshin Yu.F. ,; Zakrevskaya N.G. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop criteria and methodological approaches to the typology of physical culture. Methods and structure of the study. Analysis and generalization of literary sources and electronic resources, historical and comparative analysis, systematization. Results and conclusions. Physical culture is a complex, multifaceted social phenomenon. With the accumulation of knowledge reflecting the specificity of physical culture, there was an urgent need to develop its structure (structure) and, in particular, to identify its main structural components. The article considers various approaches to the typology of physical culture forms. The most significant and essential features of the classification of specific components of physical culture are analyzed. Taking into account the variety of forms of physical culture identified in the course of the study of literary sources, and also in connection with its disorder, a general classification of forms of physical culture has been developed. To systematize various forms, types of physical culture, it seems appropriate to use a typological approach.